EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH MENGELOLA PENDIDIKAN (STUDI DI SMP PAB 3 SAENTIS KABUPATEN DELI SERDANG) - Ari Anggara; Elfrianto Elfrianto; Amiruddin Amiruddin (EDUTECH, 2024)
Every educational unit in the national education system requires Management Standards. Management Standards contain ten components, namely Vision, Mission and Goals, Medium Term Work Plan, Annual Work Plan, Leadership, Culture, Implementation, Curriculum Development and Internal Quality Assurance, Supervision, Accountability and Management Information Systems. By fulfilling these Management Standards, it is hoped that we will be able to provide quality education and learning in order to prepare quality graduates in accordance with the objectives that have been set. Based on this, the problem formulation of this research is 1) How is the Effectiveness of the Principal at PAB 3 Saentis Middle School? 2) What are the Principal's Leadership Capabilities in Managing Education at PAB 3 Saentis Middle School? 3) Is the Principal's Leadership Effective in Managing Education at PAB 3 Saentis Middle School.This research is qualitative research with a case study approach